Tornei-me mãe, e agora? Interações entre trabalho e família na percepção de mães empreendedoras - Bandeira, Emanuella Lustosa (2023)
The relationship between work and family has attracted the attention of several researchers. The literature highlights that there are two poles resulting from this relationship: the negative (work-family conflict) and the positive (positive interface between work and family). Therefore, whether to reduce conflicts or benefit from the resources arising from the multiplicity of roles, many women, especially mothers, enter entrepreneurship. Thus, the general objective of this research is to understand how the relationships between work-family interfaces, motherhood and female entrepreneurship are characterized. To achieve this, the relationship between motherhood and the entrepreneurial path, the perception of professional success and role performance, work-family conflicts and the positive interface between work and family were investigated. This is a qualitative and descriptive study, carried out through 14 semi-structured interviews with entrepreneurial mothers who work in the clothing sector in the state of Ceará. The data were operationalized in the atlas.ti 7 software. The results indicate that the role of mother is taken into consideration when opting for entrepreneurship; professional success is understood as financial return and business growth followed by work-family balance; mothers consider their professional performance to be insufficient; they experience conflicts due to the high responsibility and excessive time available to the business; and realize that the benefits arising from work-family interfaces outweigh the incompatibilities. These greatest benefits are predominantly related to the resource of psychological capital, when marital fulfillment favors the partner's participation in domestic activities, generating security and availability for the entrepreneurial role; and the resource of development, when the skills and different perspectives developed during motherhood improve the performance of the entrepreneurial role. Therefore, the family is the largest generator of positive resources for work. This greater positive apprehension seems to be related to the profile of the interviews - middle class women - with the results being limited to this class. However, they promote the strengthening not only of themselves, but also of more vulnerable women, suggesting that female entrepreneurship has been providing conditions for protagonism and self-empowerment to a collective network of fashion women. It is warned that the transition to an entrepreneurial career can mean a return to the situation of work-family imbalance experienced in formal employment, bringing reflections on the dilemmas faced by women when trying to reconcile everything. The study fills two gaps in the national literature (research that considers the two theoretical perspectives of the work-family interface simultaneously; and that considers the connection between female entrepreneurship and motherhood) and, in this sense, presents academic, managerial and social contributions, highlighting -i) joint analysis of the different theoretical perspectives of the work-family interface; ii) contribution to the “5Ms” model by Brush, Bruin and Welter (2009), confirming that motherhood should be analyzed centrally in studies on female entrepreneurship; iii) discussion on the international phenomenon ‘mumpreneurs’; iv) balance of opportunities and restrictions generated by motherhood, highlighting the opportunities and understanding that not motherhood, but rather the father's lack of participation, acts as a professional restriction for women; v) deepening of bills and development of public and management policies aimed at family care, work-family balance and gender equity; and vi) perception of the gender variable as a social construct that reverberates in different aspects. It is suggested that future studies carry out research with women from different social classes and deepen the discussion on the positive impacts of motherhood on work and vice versa, bringing more current perspectives on the work-family relationship.